Bakakarun Transactions and Agricultural Zakat among the Banjar Community: An Islamic Law Analysis - Muhamad Rahmani Abduh; H.M. Hanafiah; Rahmat Sholihin; Mahmud Yusuf; Parman Komarudin (Fakultas Studi Islam Universitas Islam Kalimantan Muhammad Arsyad Al Banjary, 2025)
Bakakarun is a profit-sharing agricultural partnership between landowners and cultivators commonly practiced by the Banjar community. However, this practice raises two key issues under Islamic law: first, the prohibition of mukhābarah contracts in the Shafi’i school, which is predominantly followed by the Banjar; second, improper zakat payment methods, particularly regarding the calculation of nisab from shared harvests. This study employs an empirical legal approach with a descriptive qualitative method, conducted across three villages in Barito Kuala Regency, South Kalimantan. The findings reveal that the bakakarun practice aligns with the principles of mukhābarah as permitted by Imam Nawawi. Nonetheless, errors in zakat calculation persist due to the absence of khulṭah (asset pooling) in determining nisab. It is therefore recommended that zakat be deducted prior to harvest distribution to prevent avoidance of zakat obligations.